PENGUKURAN WAKTU KERJA PEMBUATAN KANOPI PADA MUTIARA GYPSUM SANGATTA - Kumala, Sapta Erna (EKONOMIA, 2013)
The purpose of this study was to determine the standard labor time kerjamemproduksikanopipada Gypsum Pearl company in Sengata . The experiment was conducted for 3 months ( April to June 2013) on Pearl Gypsum in Sangatta , which bekaitan Measurement Periods Work on Pearl Canopy Gypsum manufacture in Sangatta.Kegiatan dilakukanyaitu research : A literature study , field observations , interviews , documentation , data collection and analysis . dikupulkan data in the study include : a general overview of the company , and the organizational structure of respondents . The analytical tool used in this study is 1 ) . Average - Average time ( Adverage time ) 2 ) Nominal Time ( Norml time ) 3 . Standard Time ( Standard time ) Based on the analysis results obtained by calculation as follows : 1 ) Average time to assemble the canopy 19 hours 35 minutes 2 ) normal time producing the canopy on Pearl company in the Sengata Gypsum is 1.1736 for 55 minutes or 19 hours menit.3 ) . standard time in the company manufactures canopies Pearl Gypsum in Sengata using kelonggaraan factor by 15 % of the normal time is for 1,349 minutes or 22 hours and 48 minutes less than the average time - average produced by other employers canopy is 29 hours . Keywords : Work Time